Expanded carrier screening in the United States: A systematic evidence review exploring client and provider experiences. Issue 4 (25th February 2022) - Ramdaney, Aarti; Lichten, Lauren; Propst, Lauren; Mann, Caitlin; Lazarin, Gabriel A.; Jones, Malorie; Taylor, Amy; Malinowski, Jennifer
Abstract: The aim of carrier screening is to identify prospective parents at risk of having a pregnancy affected with an autosomal recessive or X‐linked disorder. Though minimal guideline‐based screening is available, expanded carrier screening (ECS) is quickly becoming a feasible option for the general population due to its growing availability and affordability. However, the impact of ECS on clients and providers remains relatively unexplored. We performed a systematic evidence review to identify publications describing client‐, provider‐, and test‐related outcomes. We searched several biomedical databases for articles published between January 1, 2003 and May 31, 2021. Studies were eligible for inclusion if they described genetic counseling and/or genetic testing for carrier screening (minimal guideline‐based or ECS) in a prenatal or preconception setting in the United States. Title and abstract screening were performed using the Raayan web application or customized Google Forms. Full‐text review and data extraction of included articles were performed using custom Google Forms. Two researchers performed a multistep selection process independently for validation purposes. Of 5413 unique articles screened, 36 studies were included with several studies contributing to multiple outcomes. Twenty described outcomes relating to patients/clients, 10 described provider‐based outcomes, and 16 described test‐based outcomes. Findings suggest that client and provider perceptions of ECS and minimal guideline‐based carrier screening are multifaceted. Though clients have expressed desire for ECS, clinical uptake and impact on reproductive decision‐making varies. Additionally, though genetic counselors seem to be comfortable with ECS, most other reproductive care providers seem to prefer minimal guideline or ancestry‐based screening due to perceived barriers, such as time needed for ECS results disclosure and follow‐up, as well as the desire to have panels set by professional societies/recommendations. There are limitations within the gathered literature, leading to potential uncertainty in the generalizability of our review. We outline several recommendations for future studies, including the need to examine variant interpretation and use of next‐generation sequencing.